Seismological and InSAR based investigations to characterise earthquake swarms in Jamnagar, Gujarat, India – An active intraplate region. Issue 8 (1st December 2022) - Srijayanthi, G.; Chatterjee, R.S.; Kamra, Charu; Chauhan, Mamta; Chopra, Sumer; Kumar, Santosh; Chauhan, Prakash; Limbachiya, Harsh; Champati Ray, P.K.
Abstract: A swarm type of seismic activity started near Khankotda and Matwa villages in the Jamnagar district in the middle of September 2019. 76 earthquakes belonging to this activity were well recorded and located by the network operated by the Institute of Seismological Research. The general trend of the 2019 swarm earthquakes is NW-SE, in conformity with the strike of the local lineaments and dykes. This swarm is not associated with any major faults in the region (the region is devoid of any major mapped faults), the closest being the ENE-WSW oriented North Kathiawar Fault, ∼60 km north of it. The epicentres of the 2019 swarm are in the proximity to the swarms that occurred in 2006 and 2007. Akin to the previous swarms in this region, the current one also appears to be triggered following the heavy rainfall. The focal mechanisms of 11 M > 3 earthquakes in this swarm are determined. The mechanisms reveal a reverse regime with ESE-WNW strike. We also used the Differential Interferometric Synthetic Aperture Radar (DInSAR) technique to map the surface deformation in the affected area. An uplift of ∼1.1 to 5.3 mm is noticed to the north of an ESE-WNW trending local lineament in the vicinity of the swarms with subtle fluctuations (ups and downs) during September to December 2019, which gradually stabilised. The seismicity pattern, focal mechanisms and surface deformation lead us to interpret this lineament as the seismogenic fault, which generated this swarm activity.